2018
DOI: 10.2196/preprints.10764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bring-your-own-device in medical schools and healthcare facilities: A review of the literature (Preprint)

Abstract: Background: The 'culture' or 'habit' of using personal mobile devices for work and learning

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…A significant number of these incidents occur within environments where there is a perceived lack of knowledge and understanding towards security risks and 2 where the staff does not proactively take measures to protect their devices, this is a result of an absence of effective BYOD security policies and device management practices (Curtis, 2014). Furthermore, studies have shown examples of how to create BYOD strategies and policies in hospitals using: mobile device management, data security, medical applications, information technology, education, policy, and guidelines, among other things (Kadimo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of these incidents occur within environments where there is a perceived lack of knowledge and understanding towards security risks and 2 where the staff does not proactively take measures to protect their devices, this is a result of an absence of effective BYOD security policies and device management practices (Curtis, 2014). Furthermore, studies have shown examples of how to create BYOD strategies and policies in hospitals using: mobile device management, data security, medical applications, information technology, education, policy, and guidelines, among other things (Kadimo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%